Ladybird guide to the centennial olympic games (Ladybird Books Ltd. New York, 1996)
Ladybird Guide to the Centennial Olympic Games offers a concise and accessible overview of the 1996 Summer Olympics in Atlanta, highlighting key events, athletes, and the significance of the Games in a historical context.